Measuring the Impact of Technological Pedagogical Content Knowledge on Teacher Resilience in Universities of Pakistan - Sadaf, Muddassaraha (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
The aim of this Empirical Paper is to determine the impact & linkage of Technological Pedagogical Content Knowledge with Teacher Resilience among teachers of Pakistan. Data collection was conducted in 7 universities, 5 Colleges, 3 Schools and 2 Academies including public and private educational institutes of 3 cities of Pakistan by using simple random sampling technique. Self-administered questionnaires were distributed among 425 teachers. With 92.94% response rate, 395 questionnaires were responded positively. 377 responses were found useable. Confirmatory Factor Analysis, Reliability Analysis, Frequency Distribution Analysis, Pearson’s R correlation & Multiple linear Regressions analysis techniques were used to analyze the data on SPSS PSAW version 22.The Regression model is moderately parsimonious with 52.7% of the variance. TPACK Framework on the whole have positive impact (β=.439) & have positive strong significant relationship (.702**) at the 0.002 level of significance with teacher resilience. Technology Knowledge has positive impact (β=.478) & have positive moderate significant relationship (.461**),Pedagogy Knowledge has positive impact (β=.512) & have positive moderate significant relationship (.573**),Content Knowledge has positive impact (β=.412) & have positive moderate significant relationship (.398**),Pedagogical Content Knowledge has positive impact (β=.401) & has positive moderate significant relationship (.429**), Technological Pedagogical Knowledge has positive impact (β=.295) & have positive moderate significant relationship (.322**),Technological Content Knowledge has positive impact (β=.478) & have positive moderate significant relationship (.418**),Technological Pedagogical Content Knowledge has positive impact (β=.307) & have positive moderate significant relationship (.497**) & Context Knowledge has positive impact (β=.395) & has positive moderate significant relationship (.330**) with teacher resilience. This study is significant enough to support the teachers and educational policy makers to adopt technology based pedagogical approaches to foster resilience among teachers and educational settings. By using cross sectional research design, the study was conducted in context of Pakistan. The model can be studied by scholars in future by using longitudinal & time series research design to increase generalizability.